5. Salix Extract: Impact on the Quantity of Escherichia coli in the intestines of Broiler Chickens Exposed to the Heat Stress - M Daud AK; Rivaldi Luthfi; Sugito Sugito; Andi Novita; Ismail Ismail; M Nur Salim; Fakhrurrazi Fakhrurrazi; Mahdi Abrar; Juliani Juliani (Universitas Syiah Kuala, 2021)
Escherichia coli (E. coli) is a normal flora and a facultative anaerobic bacterium that plays an essential role in the humoral nutritional metabolism of broiler intestines. This study aims to determine the effect of salix (Salix tetrasperma roxb) extract 50 and 100 mg/litre in drinking water of E. coli colonies in the broiler intestines experiencing heat stress. The sample is 12 intestines of broiler strain MB-90 aged 28 days. The method used a completely randomized design. The study by user three treatments: P0 was not given salix extract in drinking water; P1 and P2 were given salix extract 50 and 100 mg/litre in drinking water. The data were analyzed using One-way ANOVA and were continued with the Duncan test. We can conclude that the salix extract given to broiler chickens with heat stress could affect many E. coli colonies. This result can be seen from the doses given, indicating that the number of E. coli colonies in chicken intestines that experience heat stress depends on the dose of salix extract. The higher dose is given, the fewer colonies in the chicken intestine